Performance Analysis of OFDM-Based Decode-and-Forward Relay Network with Multiple Interferers over Rayleigh Fading Channels. (10th October 2010) - Tu, Jia; Cai, Yueming; Yang, Weiwei
Abstract : We consider an OFDM-based decode-and-forward relay network with multiple uncorrelated equal power interferers over frequency-selective Rayleigh fading channels and derive a unified closed-form expression of average symbol-error ratio for M -ary phase-shift-keying ( M -PSK) modulation. Simulations are carried out to validate our analyses.